Choosing a Proper Scenario of the Monetary Development and Financial Integration in the EurAsEC - Zhuk, Irina; Godes, Nadzeya (Olsztyn Economic Journal, 2014)
The article is devoted to the problem of choosing an effective scenario of monetary integration within the EurAsEC. A fundamentally new approach is that the Eurasian integration is considered to become an alternative to disintegrative tendencies of post-Soviet countries. The advisability for a common currency and a system of supranational governance structure are given on the basis of the analysis of development of EurAsEC member states. The reasonability and timeliness of this event as a basis for further development of integration processes and sustainable development of EurAsEC is substantiated.